Chalcogenide based 2D nanomaterials for supercapacitors - Raja Seman, Raja Noor Amalina; Azam, Mohd Asyadi (Springer, 2022)
To overcome the depletion of fossil fuels, current cutting-edge research is focusing on the future engineering and technologies in any energy generating devices. A supercapacitor is one of the most promising among them, with very fast charging and discharging times and good cyclic stability. Supercapacitors have been rapidly developing to meet the demand to solve energy and environmental problems. The electrochemical parameters of supercapacitor devices, such as specific capacitance, rate, cycling stabilities, energy, and power densities, are greatly influenced by the electrode materials used. Metal chalcogenide nanomaterials are highly demanded in the research of various electrodes to meet the ever-increasing energy source demands. Metal chalcogenides are strongly scrutinized as an emerging competitor due to their distinctive physical and chemical features. These materials have a lot of potential as electrode materials in supercapacitor devices. In this chapter, the outstanding performance of metal chalcogenides nanomaterials in the field of supercapacitors is summarized in terms of their electrochemical performances, demonstrating them as a very efficient electrode for supercapacitors.